Account management of the local authorities: case study from Hungary - Jakab, Tekla; Szabó, Janka Klára (Studia Mundi – Economica, 2021)
The study examines the impact of the integration of Savings Cooperatives on the account management of local governments in the framework of a questionnaire survey. In the course of the research, the authors evaluated the factors influencing the bank change within the framework of principal component analysis, cluster analysis, and cross-tabulation analysis.